2018
DOI: 10.1088/1751-8121/aaee34
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic uncertainty relation

Abstract: Relative fluctuations of observables in discrete stochastic systems are bounded at all times by the mean dynamical activity in the system, quantified by the mean number of jumps. This constitutes a kinetic uncertainty relation that is fundamentally different from the thermodynamic uncertainty relation recently discussed in the literature. The thermodynamic constraint is more relevant close to equilibrium while the kinetic constraint is the limiting factor of the precision of a observables in regimes far from e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
110
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 51 publications
1
110
0
Order By: Relevance
“…We now prove the activity bound [31]: the precision of an observable that is the weighted sum of the transitions undergone by a finite-state continuous time Markov chain during an arbitrary time interval is bounded by the mean number of transitions.…”
Section: The Activity Bound As a Periodic Uncertainty Relationmentioning
confidence: 94%
See 2 more Smart Citations
“…We now prove the activity bound [31]: the precision of an observable that is the weighted sum of the transitions undergone by a finite-state continuous time Markov chain during an arbitrary time interval is bounded by the mean number of transitions.…”
Section: The Activity Bound As a Periodic Uncertainty Relationmentioning
confidence: 94%
“…It yields an upper bound for the response of f , which reduces to (1) when the chosen perturbation results in a time rescaling of the dynamics. The entropic [23] as well as the activity bound [31] have thus been extended to both current-like and counting observables. This approach, which makes contact with inequalities originally derived by Kullback [25], has sparked much interest in the application of information theoretic results and concepts.More recently [28], the exponential bound p max = (exp σ − 1)/2 has been derived for Langevin dynamics with feedback, under the condition of validity of the detailed (joint) fluctuation theorem for σ and f .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…where the friction is increased by 1 + α without touching the diffusion constant D. Then, the second order in the action is the kinetic energy: s α = α 2 γ 2 v 2 /(4D). , and with · α the expectation in the perturbed process; see [70,71] for details. Observe that the (unperturbed) expectation A ′′ 0 is related to the frenesy as the above examples illustrate.…”
Section: Kinetic Uncertainty and The Fisher Metricmentioning
confidence: 99%
“…A connection between discrete and continuous time uncertainty relations is shown in [34]. One can also see similar uncertainty relations in the context of discrete processes [35], multidimensional systems [36], Brownian motion in the tilted periodic potential [37], general Langevin systems [38], molecular motors [39], run and tumble processes [40], biochemical oscillations [41], interacting oscillators [42], effect of magnetic field [43], linear response [44], measurement and feedback control [45], information [46], underdamped Langevin dynamics [47], timedelayed Langevin systems [48], various systems [49], etc.. Recently, Hasegawa et al [50] found an uncertainty relation for the time-asymmetric observable for the system driven by a time-symmetric driving protocol using the steady state fluctuation theorem.…”
Section: Introductionmentioning
confidence: 74%